ANALYSIS OF REINFORCED SOIL WALL CONSIDERING OBLIQUE PULL: BILINEAR FAILURE MECHANISM – LINEAR SUBGRADE RESPONSE I - P. V. S.N. P. Kumar; M. R. Madhav (International Association of Lowland Technology, 2009)
The available methods of analysis and design of reinforced soil walls consider only the axial pullout of the reinforcement. But, in practice, the reinforcement is subjected to oblique pull because of which the backfill below the reinforcement deforms transversely mobilizing normal stresses at the interface. As a result, the shear resistance mobilized along the reinforcement – backfill interface could be different and considerably more in case of oblique pull compared to the value corresponding to only axial pull. A new method to estimate the mobilized transverse forces in reinforced soil wall is presented. A modified factor of safety is defined, estimated and compared with the conventional one to establish the significance and contribution of the mobilized transverse forces. A parametric study quantifies the contributions of the global subgrade stiffness factor, length of reinforcement, the oblique or transverse displacement, and angle of shearing resistance of the backfill, interface friction angle and the number of reinforcement layers on the modified factor of safety and improvement ratio.